Analysis of Risk Factors for Pregnancy Complications Based on Maternal and Child Health Data in Primary Midwifery Services - Dewi Susanti (Jurnal Ners, 2026)
Pregnancy complications remain a major challenge in maternal health care, particularly in the obstetric referral system from primary health care facilities. The high number of referrals often reflects the presence of undetected or inadequately managed maternal risk factors from the outset. This study aims to identify maternal risk factors associated with pregnancy complications in obstetric referral cases from Basic Emergency Obstetric and Neonatal Care (PONED) facilities throughout 2025. This study used a quantitative approach with an analytical observational design based on secondary data, which was analyzed through bivariate tests and multivariate logistic regression to identify independent risk factors. The results showed that severe preeclampsia was the most dominant referral indication, while hypertension in pregnancy, maternal anemia, gestational age less than 37 weeks, and a history of obstetric complications were significantly associated with the occurrence of pregnancy complications. After controlling for confounding variables, hypertension in pregnancy and maternal anemia remained the most consistent risk factors. These findings confirm that maternal clinical conditions play an important role in determining the level of obstetric urgency and the need for referral. Conceptually and practically, these results contribute to strengthening the risk-based antenatal care approach at the primary care level and provide an empirical basis for strengthening early detection, referral decision-making, and efforts to prevent pregnancy complications to improve maternal safety